QOL-40. THE IMPACT OF TASK COMPLEXITY ON INFORMATION PROCESSING SPEED AND NEURAL COMMUNICATION IN PAEDIATRIC BRAIN TUMOUR SURVIVORS. (4th December 2020) - Cox, Elizabeth; Atton, Juanita; Tseng, Julie; Bells, Sonya; de Medeiros, Cynthia; Laughlin, Suzanne; Bouffet, Eric; Mabbott, Donald J
Abstract: Paediatric brain tumour survivors (PBTS) experience slower information processing speed (IPS) that contributes to difficulty performing tasks of minimal (MC) and greater complexity (GC), and is related to aberrant neural communication. It is still unknown whether deficient IPS exists during increasing complexity. We aim to determine if PBTS experience deficient IPS and neural communication relative to typically developing children (TDC) during an increasingly complex visual-motor reaction time (RT) task. During magnetoencephalography recording, participants ( n =58, 12.69 ±3.24 years) pressed a button with their left or right thumb after an arrow pointing in the corresponding direction appeared on a screen. During two MC conditions, the arrow pointed in a single direction. During a GC condition, the arrow alternated direction randomly. Mean RT >3SD and signal artifacts were removed prior to analyses. The phase lag index (PLI) estimated neural communication between 90 cortical sources. Linear regression and Network Based Statistics assessed group differences in mean RT and the PLI. PBTS demonstrated increased RT relative to TDC during the GC condition ( p =0.04, M PBTS =354.00s, M TDC =326.00s). Group differences in mean RT during MC conditions and the PLI during all conditions were not detected ( p >0.05). These results suggest PBTS experience slower IPS during GC. Reduced IPS is thought to contribute to difficulty recruiting cognitive resources needed to perform more complex tasks. Subtle deficits in neural communication may underlie slower IPS. The weighted PLI is superior to the PLI when estimating small differences in neural communication. We will now use the weighted PLI to assess task-related neural communication.